Analyzing the Efficiency of Teaching Methods: The Use of Eclectic Methods to Improve Language Proficiency for EFL Learners in Indonesia - Mareta Cahyada (UPT Perpustakaan Universitas Jambi, 2025)
Choosing the proper teaching method is a challenge faced by educators. They sometimes need help determining teaching methods if they only use a single method. To minimize this, teachers can use the eclectic method, a combination of several more significant methods. This study aims to investigate the effectiveness of the eclectic approach in improving English as a Foreign Language (EFL) proficiency among Indonesian learners This research will explore the theoretical underpinnings, advantages, challenges and practical applications of the eclectic approach through a comprehensive literature review. By reviewing research findings, this study will provide insights into the potential benefits of this method in promoting language development and critical thinking skills. In addition, it will also discuss strategies for effective implementation, including curriculum design, teacher training and technology integration. The findings of this study will contribute to the ongoing discourse on effective language teaching methodologies and inform pedagogical practices in Indonesian classrooms.